2022
DOI: 10.1186/s12974-022-02549-0
|View full text |Cite
|
Sign up to set email alerts
|

Nilotinib modulates LPS-induced cognitive impairment and neuroinflammatory responses by regulating P38/STAT3 signaling

Abstract: Background In chronic myelogenous leukemia, reciprocal translocation between chromosome 9 and chromosome 22 generates a chimeric protein, Bcr-Abl, that leads to hyperactivity of tyrosine kinase-linked signaling transduction. The therapeutic agent nilotinib inhibits Bcr-Abl/DDR1 and can cross the blood–brain barrier, but its potential impact on neuroinflammatory responses and cognitive function has not been studied in detail. Methods The effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Recent studies have reported that chronic LPS administration promotes neuroinflammation-mediated cognitive disruption [ 42 , 43 , 44 , 45 ] and that low-dose (250 μg/mL) chronic LPS administration induces motor and short-term working memory impairment in wild-type mice [ 46 ]. Based on these observations, we used a low dose of LPS to evaluate the effects of the L-type CCB felodipine on chronic neuroinflammation-mediated learning and memory impairments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported that chronic LPS administration promotes neuroinflammation-mediated cognitive disruption [ 42 , 43 , 44 , 45 ] and that low-dose (250 μg/mL) chronic LPS administration induces motor and short-term working memory impairment in wild-type mice [ 46 ]. Based on these observations, we used a low dose of LPS to evaluate the effects of the L-type CCB felodipine on chronic neuroinflammation-mediated learning and memory impairments.…”
Section: Resultsmentioning
confidence: 99%
“…No. DYC4198-5, R&D Systems, Minneapolis, MN, USA) as previously described [ 46 ]. The conditioned medium used in the ELISA was harvested from cells and treated successively with 5 μM felodipine or vehicle for 30 min and with 200 ng/mL LPS or PBS for 5.5 h. The ELISA was conducted according to the provided protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Primary microglia were isolated and purified from C57BL6/J mice within 3 days of birth as described previously [ 39 ]. Briefy, cerebral cortex was isolated, fltered through a 70-μm nylon mesh, and then cultured in low-glucose DMEM medium supplemented with 10% FBS and 1% penicillin/streptomycin at 37°C under 5% CO2 incubator.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the effects of varlitinib on glial activation, we measured Iba-l and GFAP fluorescence intensity. In addition, to investigate the effects of varlitinib on glial migration and morphology, we quantified the number of GFAP-positive cells and the percent GFAP-positive area, respectively ( 16 , 21 ).…”
Section: Methodsmentioning
confidence: 99%